Quality of life and functional outcome in surgically treated ankle fractures in diabetics and non diabetics - Kishan Rao Subramaniam (Kulliyyah of Medicine, International Islamic University Malaysia, 2020)
Ankle fractures are fractures involving the bones around the ankle joint. Ankle fractures are among the commonest fractures in Malaysian population especially in young adults due to motor vehicle accidents, and also in elderly population due to osteoporotic bone. This injury can be treated either non surgically or by surgical method. While surgical method is typically reserved for displaced fractures, diabetes mellitus is also a known risk factor for increased post-operative complications. Therefore, research is needed to confirm the effect of diabetes on patients with post-operative ankle fractures. The aim of this study was to observe the quality of life and functional outcomes in adult diabetic patients in comparison to the non-diabetics. By using quantitative method and retrospective study design, the study was conducted over a period of 52 months from January 2014 to May 2018 involving 60 patients (47 diabetics and 13 non-diabetics) who underwent surgery for ankle fractures in two medical centres in Malaysia, namely Hospital Tengku Ampuan Afzan (HTAA) and International Islamic University Malaysia Medical Centre (IIUMC). Olerud-Molander ankle scoring system (OMAS) was used to evaluate participants' functional outcomes, while SF-36 questionnaire was utilised to measure their quality of life. The findings revealed that majority of patients without diabetes mellitus (n = 35) obtained marks between 61-90 for OMAS score, which indicate the 'Good' outcome, while several others (n = 6) scored between 91-100, signifying the 'Excellent' outcome. On the other hand, patients with diabetes mellitus generally scored either in the range of 31-60 ('Fair' outcome) or 0-30 ('Poor' outcome). Further analysis also revealed a statistically significant association between patients' diabetes status and OMAS score (p-value <0.01). This suggests that patients without diabetes have better functional outcome as compared to those with diabetes. In regards to quality of life, diabetic patients obtained lower mean values than the non-diabetic patients for both SF36 physical and mental component summary scores (lower by 0.22 and 0.14 respectively). As compared to those without diabetes, diabetic patients tend to have lower level of self-esteem towards their quality of life, either physically or mentally. An important implication of the study findings is pertaining to the importance of considering diabetic presence as a prominent factor influencing patients' physical and mental well-beings after the surgery. Specific measures involving a multidisciplinary approach must be taken in order to reduce the impact of post-operative complications, particularly among diabetic individuals who are more exposed to severe infections, contamination, and other risks of physical and mental health. This warrants the need for a consideration of both physical and psychological supports for diabetic patients. To conclude, this study supported that diabetes has a prominent role in influencing patients' functional outcomes and perceived quality of life following their surgically treated ankle fracture. Therefore, it is suggested that necessary pre- and post-operative diabetic management procedures should be outlined for patients with ankle fracture injuries in this country.